Introduction To Zen Training. - Omori (Taylor and Francis, 2012)
When Buddha Said that We suffer because of our attachments, he was describing the condition in which we view the world from the perspective of our ego, that part of us that sags fundamentally we are each individual, apart from all that surrounds us. Buddhism in general is a religion that leads to a deeper perspective, that all existence is part of the Whole. While many people find that a meaningful belief, Zen Buddhism takes a slightly different position: don't believe a lofty religious ideal. All of you - flesh and blood, thoughts and emotions - can experience the Whole directly at all times.